High-performance desert sand foam concrete and preparation method thereof
Through the synergistic effect of composite activator, roughened PET fiber and alkali-activated metakaolin composite microspheres, the strength and durability problems of foamed concrete in low-temperature freeze-thaw saline water environment were solved, and early strength development and long-term performance improvement were achieved.
Patent Information
- Application Number
- CN202511727974.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-24
- Publication Date
- 2026-01-23
- Estimated Expiration
- 2045-11-24
AI Technical Summary
Existing foamed concrete cannot simultaneously meet the requirements of strength development, durability and freeze-thaw resistance in low-temperature freeze-thaw saline water environments. Existing technologies lack synergy, resulting in poor material performance in extreme environments.
A combination of composite activator, roughened PET fiber and alkali-activated metakaolin composite microspheres is used to promote low-temperature hydration, relieve freeze-thaw stress and solidify chloride ions to form a dense microstructure to enhance freeze-thaw resistance.
It significantly improves the early strength development and long-term durability of concrete in low-temperature freeze-thaw saline water environments, effectively inhibits salt crystallization and steel corrosion, and achieves high-performance performance of the material in extreme environments.
Abstract
Description
Technical Field
[0001] This invention relates to the field of concrete technology, and more specifically, to a high-performance desert sand foamed concrete and its preparation method. Background Technology
[0002] Foamed concrete was initially widely used as an engineering insulation material, such as insulation layers for tunnel structures in cold regions, energy-dissipating layers for high-stress soft rock tunnel structures, roadbed filling layers, and building insulation walls. In recent years, its application has expanded to roadbed filling as a replacement layer and to the lining structures of high-stress soft rock tunnels as a buffer energy-dissipating layer. In infrastructure construction in cold, high-latitude coastal and salt lake regions, foamed concrete has attracted considerable attention due to its lightweight and excellent insulation properties. However, the extreme environments prevalent in these regions, including low temperatures, freeze-thaw cycles, and scarcity of freshwater resources (only local saline water can be used), pose severe challenges to traditional foamed concrete technology. Existing foamed concrete technologies face three main technical bottlenecks when dealing with these complex environmental factors:
[0003] 1. Hydration stagnation and insufficient early strength development under low-temperature conditions
[0004] In conventional foamed concrete, the cement hydration reaction rate drops sharply below 5°C, resulting in extremely slow or even complete halt in early strength development. This not only prolongs the demolding and construction cycle but also makes the concrete highly susceptible to frost damage before achieving sufficient strength. Although existing technologies employ accelerators and antifreeze agents (such as chlorides and nitrites) to promote low-temperature hydration, these admixtures often introduce harmful ions, threatening long-term durability, and may produce side effects due to salt crystallization in high-concentration saline environments.
[0005] 2. Durability deteriorates rapidly under harsh freeze-thaw conditions.
[0006] When foamed concrete is saturated with water and subjected to freeze-thaw cycles, the expansion stress generated by the repeated phase changes of pore water leads to cracking and spalling of the pore walls, causing a rapid decrease in the dynamic elastic modulus. Traditional techniques mainly rely on introducing air-entraining agents to create closed-cell bubbles to buffer freeze-thaw stress. However, when using desert sand with a low fineness modulus and poor particle size distribution, solid particle settling and bubble rising coexist, making it difficult to form a stable and uniform pore structure system. Single physical air-entraining measures have very limited effect on improving durability under the combined effects of long-term freeze-thaw cycles and salt crystallization in saline water.
[0007] 3. Mixing with salt water leads to deterioration of the internal chemical environment and salt freezing damage.
[0008] While directly using seawater, salt lake water, or groundwater to mix concrete solves the freshwater shortage problem, it introduces high concentrations of harmful components such as chloride and sulfate ions. These ions not only disrupt the stability of cement hydration products, leading to a decline in strength later on, but also couple with freeze-thaw cycles to produce a salt-freezing effect—the superposition of salt crystallization pressure and ice expansion stress—accelerating material damage. Furthermore, free chloride ions significantly increase the risk of corrosion of internal reinforcing steel. Existing chloride-fixing technologies (such as incorporating nitrates and rust inhibitors) have mostly proven effective in ambient freshwater environments; their long-term effectiveness under the combined effects of low temperatures, saltwater, and freeze-thaw cycles remains unclear, and they cannot solve the problem of physical expansion caused by salt crystallization.
[0009] In summary, existing technical solutions are mostly designed to address single problems and lack a systematic strategy for dealing with the complex environment of low-temperature freeze-thaw saline water. For example, measures to promote low-temperature hydration may exacerbate salt crystallization, while air-entraining methods to improve freeze resistance may be detrimental to strength development. The various technical approaches lack synergy and even hinder each other, making it difficult to meet the requirements for long lifespan and high durability of engineering materials in special environments such as polar regions and cold-region saline lakes. Summary of the Invention
[0010] The technical problem to be solved by the present invention is that existing foamed concrete is difficult to withstand the strength and durability requirements of the complex environment of low temperature freeze-thaw saline water. In order to overcome the above-mentioned defects of the prior art, the present invention provides a high-performance desert sand foamed concrete and its preparation method.
[0011] The technical solution of this invention is: a high-performance desert sand foamed concrete, comprising the following components by weight:
[0012] 70 parts silicate cement, 30 parts fly ash, 20-100 parts desert sand, 25-35 parts saline water, 0.2-0.5 parts foaming agent, 5-12 parts composite activator, 5-15 parts alkali-activated metakaolin composite microspheres, and 0.5-2 parts roughened PET polymer fiber;
[0013] The composite activator is formulated as follows by weight ratio: calcined phosphogypsum: alkaline slag: nano silica: silica fume: 5% mass concentration polyvinyl alcohol = (40-50): (30-40): (10-15): (5-10): (10-15);
[0014] The formula for alkali-activated metakaolin composite microspheres is as follows by weight: fly ash cenospheres: metakaolin: water glass: sodium hydroxide: deionized water = 100: (20-30): (15-25): (3-5): (20-30);
[0015] Roughened PET polymer fiber is obtained by melt spinning waste PET plastic into fiber, introducing carboxyl functional groups through alkali treatment, and then growing nano-sized calcium oxalate on the fiber surface through hydrothermal method.
[0016] The nano-silica in the composite activator can effectively promote the deposition of hydration products and reduce the nucleation barrier under low temperature conditions; phosphogypsum decomposes to release SO4. 2- The formation of ettringite, accompanied by exothermic reactions, helps maintain the system temperature and continuously improve density in negative temperature environments, thus ensuring the early strength development of concrete. Roughened PET fibers refine ice crystals, alleviate frost heave stress, and synergistically with alkali-activated metakaolin composite microspheres to disperse and absorb stress, jointly enhancing freeze-thaw resistance. The closed-cell structure inside modified fly ash cenospheres provides a buffer space for ice crystal expansion, further absorbing frost heave energy. The synergistic effect of these three components significantly improves the freeze-thaw resistance of concrete. Furthermore, the system hydration forms a dense microstructure mainly composed of CSH gel, geopolymer, and ettringite, effectively blocking chloride ion migration; the alkali-activated metakaolin composite microspheres, with their ion exchange capacity, fix free chloride ions, and, combined with the highly alkaline environment of the system, promote chloride ion stabilization, significantly reducing the concentration of free chloride ions in the pore fluid and inhibiting the risk of salt crystallization and steel corrosion.
[0017] In one possible implementation, the foaming agent is sodium dodecyl sulfate or α-olefin sulfonate.
[0018] In one possible implementation, the composite activator is a core-shell particle, with a core of slow-release sulfate crystals, an intermediate layer of fine alkaline slag powder, and an outer shell of a composite layer of nano-silica and silica fume. The particle size of the core-shell particles is 30-80 μm. The outer shell first dissolves to provide nucleation sites, the intermediate layer establishes an alkaline environment to activate the cementitious material, and the core slowly releases sulfate ions to continuously promote strength development, forming a precise activation process "from the surface to the interior, from fast to slow".
[0019] In one possible implementation, the composite activator is prepared by the following method: S11, calcined phosphogypsum and alkaline slag are ground separately, and nano-silica and silica fume are mixed evenly in a dry state for later use; S12, calcined phosphogypsum powder is placed in a fluidized bed granulator and atomized PVA solution is sprayed in to granulate and form a core; S13, PVA solution is continuously sprayed in during the granulation process, and fine alkaline slag powder is added to form an intermediate layer outside the core; S14, while maintaining the fluidized state, dilute PVA solution is sprayed in, and a mixture of nano-silica and silica fume is added to form an outer shell outside the intermediate layer; S15, the granulated wet particles are dried and sintered to obtain core-shell particles.
[0020] In the above scheme, calcined phosphogypsum provides slow-release sulfate ions, alkaline slag provides alkaline excitation, nano-silica provides early nucleation sites and controls ion migration, silica fume and nano-silica work synergistically to fill and enhance the density of the outer shell, and PVA solution acts as a binder to attach these functional components to the core.
[0021] In one possible implementation, the particle size of the parent nucleus is controlled to be 30-50 μm.
[0022] And / or, the concentration of the PVA solution is 5% by mass.
[0023] And / or, the concentration of the dilute PVA solution is 3% by mass.
[0024] And / or, the drying temperature is 80-100℃, the sintering temperature is 600-700℃, and the sintering time is 0.5-2h.
[0025] In one possible implementation, alkali-activated metakaolin composite microspheres are prepared by the following method: S21, dissolve sodium hydroxide in a portion of deionized water, cool to room temperature, slowly add water glass, stir evenly, and allow to stand for aging to obtain a composite alkali activator; S22, mix metakaolin with the remaining deionized water, stir evenly, add the composite alkali activator, and continue stirring to form an alkali-activated metakaolin slurry; S23, place fly ash cenospheres in a low-speed mixer or coating pan, and spray the alkali-activated metakaolin slurry while stirring to obtain slurry-coated cenospheres; S24, seal and cure the cenospheres coated with the slurry obtained in step S23 at room temperature, and then dry to remove water to obtain alkali-activated metakaolin composite microspheres.
[0026] In the above scheme, fly ash cenospheres serve as lightweight aggregate, providing a hollow structure for mechanical cushioning; metakaolin provides activated alumina and silica to form a gel with ion exchange capacity; water glass acts as an alkali activator and binder to bond the metakaolin to the lightweight aggregate; sodium hydroxide adjusts the modulus of water glass to provide additional alkalinity; and deionized water serves as a solvent to adjust the slurry viscosity.
[0027] In one possible implementation, the sealing and curing conditions in step S24 are 15-25°C, humidity >90%, and time 20-28h; the drying temperature is 60-80°C, and the drying time is 6-8h.
[0028] In one possible implementation, the preparation parameters for the roughened PET polymer fiber are as follows: melt spinning temperature of 260-280℃, spinning speed of 200-400 m / min, and fiber diameter of 20-50 μm; after spinning, the fiber is treated with a 5-8% (w / w) sodium hydroxide solution at 70-80℃ for 1-2 h to introduce carboxyl functional groups; the alkali-treated fiber is then immersed in a 0.1-0.3 mol / L mixed solution of sodium oxalate and calcium chloride and subjected to a hydrothermal reaction at 120-150℃ for 2-4 h to obtain the roughened PET polymer fiber.
[0029] This invention also provides a method for preparing high-performance desert sand foamed concrete, comprising the following steps:
[0030] S1. Dry mix silicate cement, fly ash, desert sand, and composite activator at a speed of 150-250 rpm for 2-3 minutes.
[0031] S2. Add saline water and alkali-activated metakaolin composite microspheres to the dry-mixed material obtained in step S1, and continue to stir and mix at a speed of 300-400 rpm for 3-4 minutes.
[0032] S3. Add roughened PET polymer fibers and foaming agent to the mixture obtained in step S2, and continue stirring and mixing at a speed of 80-150 rpm for 1-2 minutes to obtain high-performance desert sand foam concrete.
[0033] In one possible implementation, there is a 30-second pause between each step, and the total stirring time for all steps is controlled to be 6-9 minutes.
[0034] The beneficial effects of this invention are as follows:
[0035] This invention systematically solves the technical challenges of low-temperature, freeze-thaw, and saline water environments through the synergistic effect of composite activators, roughened PET fibers, and alkali-activated metakaolin composite microspheres: the composite activator releases heat while promoting low-temperature hydration, providing early temperature protection for the system; the fibers and microspheres work together to buffer the system, significantly enhancing freeze-thaw resistance by refining ice crystals, dispersing stress, and absorbing expansion; the microspheres further work synergistically with the high-alkali environment of the system to solidify chloride ions, effectively inhibiting salt crystallization and steel corrosion, thereby achieving an overall improvement in strength development and durability. Detailed Implementation
[0036] The desert sand was taken from the Tengger Desert, and the saline water was taken from the salt lake area of the Qaidam Basin in Qinghai Province. Its main chemical composition (based on ion concentration) is: Cl... - 150-200 g / L, SO4 2- 20-40 g / L, Na + 80-120 g / L, Mg2+ 30-50 g / L, K + 10-20 g / L, total salinity range is 300-450 g / L.
[0037] Testing standards: compressive strength according to GB / T 50081; freeze-thaw cycle performance according to GB / T 50082; free chloride ion content according to GB / T 50476.
[0038] Example 1
[0039] This embodiment uses the following raw materials in parts by weight: 70 parts silicate cement, 30 parts fly ash, 60 parts desert sand, 30 parts saline water, 0.35 parts sodium dodecyl sulfate, 8 parts composite activator (component A), 10 parts alkali-activated metakaolin composite microspheres (component B), and 1 part roughened PET polymer fiber (component C).
[0040] The preparation process of component A is as follows: calcined phosphogypsum and alkaline slag are ground to a specific surface area ≥400 m² / kg. Nano-silica and silica fume are mixed evenly in a dry state and set aside. Calcined phosphogypsum powder is placed in a fluidized bed granulator and atomized 5% mass concentration polyvinyl alcohol (PVA) solution is sprayed in to granulate and form a core with a particle size of 30-50 μm. During the granulation process, 5% mass concentration PVA solution is continuously sprayed in and alkaline slag fine powder is added to form an intermediate layer outside the core. While maintaining the fluidized state, 3% mass concentration dilute PVA solution is sprayed in and a mixture of nano-silica and silica fume is added to form an outer shell outside the intermediate layer. The granulated wet particles are dried at 90℃ for 1 h and then sintered at 650℃ for 1 h to obtain a composite activator of core-shell particles with a particle size of 30-80 μm.
[0041] The preparation process of component B is as follows: Sodium hydroxide is dissolved in a portion of deionized water, and after cooling to room temperature, water glass is slowly added, stirred evenly, and allowed to stand for aging for 24 hours to obtain a composite alkali activator; metakaolin is mixed with the remaining deionized water, stirred evenly, and the composite alkali activator is added, and stirring is continued to form an alkali-activated metakaolin slurry; fly ash cenospheres are placed in a low-speed mixer, and the alkali-activated metakaolin slurry is sprayed in while stirring to obtain slurry-coated cenospheres; the cenospheres coated with the obtained slurry are sealed and cured at 20℃ and humidity >90% for 24 hours, and then dried at 70℃ for 7 hours to obtain alkali-activated metakaolin composite microspheres.
[0042] The preparation process of component C is as follows: waste PET plastic is melt-spun at 270℃ at a spinning speed of 300 m / min to obtain PET fibers with a fiber diameter of 30 μm; the fibers are immersed in a 6% (w / w) sodium hydroxide solution and treated at 75℃ for 1.5 h to introduce carboxyl functional groups; then the fibers are immersed in a mixed solution of 0.2 mol / L sodium oxalate and 0.2 mol / L calcium chloride and hydrothermally reacted at 130℃ for 3 h to grow nano-sized calcium oxalate crystals on the fiber surface, thus obtaining roughened PET polymer fibers.
[0043] The concrete preparation process includes: first, dry mixing silicate cement, desert sand, and component A at 200 rpm for 2.5 min; then adding salt water and component B and continuing mixing at 350 rpm for 3.5 min; finally adding component C and the foam generated by sodium dodecyl sulfate at 115 rpm for 1.5 min.
[0044] The prepared high-performance desert sand foamed concrete was poured, and the specimens were sealed and cured at 5°C for 48 hours. They were then transferred to a standard curing chamber at 20°C and humidity ≥95% for continued curing until the specified age. Compressive strength, freeze-thaw cycle mass loss, and free chloride ion content were then tested.
[0045] Performance results: After testing, the compressive strength was 5.8 MPa after 48 hours and 25.3 MPa after 28 days.
[0046] After 50 freeze-thaw cycles, the mass loss rate was 1.2%, and the internal free chloride ion content at 28 days was 0.052 wt%.
[0047] Example 2
[0048] This embodiment moderately increases the dosage of key functional components based on Example 1. Specifically, it includes 10 parts of composite activator, 12 parts of alkali-activated metakaolin composite microspheres, 1.5 parts of roughened PET polymer fiber, and the types and quantities of other raw materials are the same as in Example 1.
[0049] Performance results: Compressive strength after 48 hours: 7.1 MPa; Compressive strength after 28 days: 28.5 MPa. Mass loss rate after 50 freeze-thaw cycles: 0.8%; Relative dynamic modulus of elasticity: 95%. Internal free chloride ion content at 28 days: 0.041 wt%.
[0050] Comparative Example 1:
[0051] Formulation: This comparative example aims to examine the key role of the composite activator. Component A is not used at all in its formulation, and the other components are the same as in Example 1.
[0052] Performance results: Compressive strength after 48 hours: 0.9 MPa; Compressive strength after 28 days: 18.7 MPa. Mass loss rate after 50 freeze-thaw cycles: 4.5%; Relative dynamic modulus of elasticity: 65%. Internal free chloride ion content at 28 days: 0.048 wt%.
[0053] Comparative Example 2:
[0054] Formulation: This comparative example removes the chemical purification and buffering unit, i.e., component B (0 parts) is not used, while the other components are the same as in Example 1.
[0055] Preparation and curing: The preparation process and curing system are consistent with those in Example 1.
[0056] Performance results: Compressive strength after 48 hours: 5.5 MPa; Compressive strength after 28 days: 24.8 MPa. Mass loss rate after 50 freeze-thaw cycles: 2.8%; Relative dynamic modulus of elasticity: 82%. Internal free chloride ion content at 28 days: 0.108 wt%.
[0057] Comparative Example 3:
[0058] Formulation: The fiber reinforcement phase was removed in this comparative example, i.e., component C (0 parts) was not used, while the other components and amounts were the same as in Example 1.
[0059] Preparation and curing: The preparation process and curing system are consistent with those in Example 1.
[0060] Performance results: Compressive strength after 48 hours: 5.3 MPa; Compressive strength after 28 days: 25.1 MPa. Mass loss rate after 50 freeze-thaw cycles: 3.5%; Relative dynamic modulus of elasticity: 78%. Internal free chloride ion content at 28 days: 0.054 wt%.
[0061] In summary, the above are merely specific embodiments of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
Claims
1. A high-performance desert sand foamed concrete, characterized in that, It comprises the following components by weight: 70 parts silicate cement, 30 parts fly ash, 20-100 parts desert sand, 25-35 parts saline water, 0.2-0.5 parts foaming agent, 5-12 parts composite activator, 5-15 parts alkali-activated metakaolin composite microspheres, and 0.5-2 parts roughened PET polymer fiber; The composite activator is formulated as follows by weight ratio: calcined phosphogypsum: alkaline slag: nano silica: silica fume: 5% mass concentration polyvinyl alcohol = (40-50): (30-40): (10-15): (5-10): (10-15); The formula for the alkali-activated metakaolin composite microspheres is as follows by weight: fly ash cenospheres: metakaolin: water glass: sodium hydroxide: deionized water = 100: (20-30): (15-25): (3-5): (20-30); The roughened PET polymer fiber is obtained by melt spinning waste PET plastic into fibers, introducing carboxyl functional groups through alkali treatment, and then growing nano-sized calcium oxalate on the fiber surface through a hydrothermal method.
2. The high-performance desert sand foamed concrete according to claim 1, characterized in that, The foaming agent is sodium dodecyl sulfate or α-olefin sulfonate.
3. The high-performance desert sand foamed concrete according to claim 1, characterized in that, The composite activator is a core-shell particle, with a core of slow-release sulfate crystals, an intermediate layer of fine alkaline slag powder, and an outer shell of a composite layer of nano-silica and silica fume, and the particle size of the core-shell particle is 30-80μm.
4. The high-performance desert sand foamed concrete according to claim 3, characterized in that, The composite activator is prepared by the following method: S11, calcined phosphogypsum and alkaline slag are ground separately, and nano-silica and silica fume are mixed evenly in a dry state for later use; S12, calcined phosphogypsum powder is placed in a fluidized bed granulator and atomized PVA solution is sprayed in to form a core; S13, PVA solution is continuously sprayed in during the granulation process, and fine alkaline slag powder is added to form an intermediate layer outside the core; S14, while maintaining the fluidized state, dilute PVA solution is sprayed in, and a mixture of nano-silica and silica fume is added to form an outer shell outside the intermediate layer; S15, the granulated wet particles are dried and sintered to obtain core-shell particles.
5. The high-performance desert sand foamed concrete according to claim 4, characterized in that, The particle size of the parent nucleus particles is controlled to be 30-50 μm. And / or, the concentration of the PVA solution is 5% by mass. And / or, the concentration of the dilute PVA solution is 3% by mass. And / or, the drying temperature is 80-100℃, the sintering temperature is 600-700℃, and the sintering time is 0.5-2h.
6. The high-performance desert sand foamed concrete according to claim 1, characterized in that, The alkali-activated metakaolin composite microspheres are prepared by the following method: S21, Sodium hydroxide is dissolved in part of deionized water, and after cooling to room temperature, water glass is slowly added, stirred evenly, and allowed to stand for aging to obtain a composite alkali activator; S22, Metakaolin is mixed with the remaining deionized water, stirred evenly, the composite alkali activator is added, and stirring is continued to form an alkali-activated metakaolin slurry; S23, Fly ash cenospheres are placed in a low-speed mixer or coating pan, and the alkali-activated metakaolin slurry is sprayed in while stirring to obtain slurry-coated cenospheres; S24, The cenospheres coated with the slurry obtained in step S23 are sealed and cured at room temperature, and then dried to remove water to obtain alkali-activated metakaolin composite microspheres.
7. The high-performance desert sand foamed concrete according to claim 6, characterized in that, The sealing and curing conditions in step S24 are 15-25℃, humidity >90%, and time 20-28h; the drying temperature is 60-80℃ and the drying time is 6-8h.
8. The high-performance desert sand foamed concrete according to claim 1, characterized in that, The preparation parameters for roughened PET polymer fibers are as follows: melt spinning temperature is 260-280℃, spinning speed is 200-400 m / min, and fiber diameter is 20-50 μm; after spinning, the fibers are treated with a 5-8% mass concentration sodium hydroxide solution at 70-80℃ for 1-2 h to introduce carboxyl functional groups. The alkali-treated fibers are immersed in a mixed solution of sodium oxalate and calcium chloride at 0.1-0.3 mol / L and subjected to hydrothermal reaction at 120-150℃ for 2-4 h to obtain roughened PET polymer fibers.
9. The method for preparing high-performance desert sand foamed concrete according to any one of claims 1-8, characterized in that, Includes the following steps: S10. Dry mix silicate cement, fly ash, desert sand, and composite activator at a speed of 150-250 rpm for 2-3 minutes. S20. Add saline water and alkali-activated metakaolin composite microspheres to the dry-mixed material obtained in step S10, and continue stirring and mixing at 300-400 rpm for 3-4 minutes. S30. Add roughened PET polymer fiber and foaming agent to the mixture obtained in step S20, and continue stirring and mixing at a speed of 80-150 rpm for 1-2 minutes to obtain high-performance desert sand foam concrete.
10. The preparation method according to claim 9, characterized in that, Let the mixture rest for 30 seconds between each step, and control the total stirring time for all steps to 6-9 minutes.
Citation Information
Patent Citations
Low density grade inorganic nonmetallic solid buoyancy material and preparation method thereof
CN108083698A
Phosphogypsum-based high-strength impervious filling material and preparation process thereof
CN120682009A